2021
DOI: 10.1111/ajt.16529
|View full text |Cite
|
Sign up to set email alerts
|

Center variation in long-term outcomes for socioeconomically deprived children

Abstract: A substantial and compelling body of evidence demonstrates that social determinants of health-where we live, eat, sleep, and play-impact health. 1 Social determinants are particularly relevant after transplant because self-management capacity influences medication adherence 2 and graft health. 3 We previously demonstrated that neighborhood-level socioeconomic deprivation, a composite measure derived from US Census Bureau data, is associated with patient-level posttransplant morbidity and mortality. 2,3 An outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 31 publications
(80 reference statements)
1
35
0
Order By: Relevance
“…High‐performing pediatric liver transplantation centers were able to achieve good long‐term posttransplant outcomes despite caring for predominately socioeconomically deprived children. [ 32 ] This study demonstrated that although socioeconomic deprivation is a risk factor for adverse outcomes, there may be transplant‐center practices that mitigate the risks of socioeconomic deprivation. In addition to socioeconomic deprivation, insurance has additionally been used as a proxy for socioeconomic status.…”
Section: Socioeconomic Disparitiesmentioning
confidence: 95%
See 1 more Smart Citation
“…High‐performing pediatric liver transplantation centers were able to achieve good long‐term posttransplant outcomes despite caring for predominately socioeconomically deprived children. [ 32 ] This study demonstrated that although socioeconomic deprivation is a risk factor for adverse outcomes, there may be transplant‐center practices that mitigate the risks of socioeconomic deprivation. In addition to socioeconomic deprivation, insurance has additionally been used as a proxy for socioeconomic status.…”
Section: Socioeconomic Disparitiesmentioning
confidence: 95%
“…This would allow for national benchmarking with the ability to compare and identify high‐performing centers. [ 32 ] Moreover, pediatric transplant societies should highlight high‐performing centers, amplified through learning networks such as the Starzl Network and quality improvement initiatives such as through SPLIT to rapidly identify strategies for achieving health equity for all children requiring liver transplantation.…”
Section: Addressing Disparities In Pediatric Liver Transplantationmentioning
confidence: 99%
“…[ 4 ] We and others have described racial and socioeconomic disparities in long‐term outcomes, with Black children and children from socioeconomically deprived neighborhoods having increased risk of adverse long‐term outcomes. [ 5–8 ] However, these studies have been at the population level and therefore are not granular enough to identify actionable interventions to narrow these disparities. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…For example, just as 1‐year and 3‐year survival outcomes are publicly reported, regulatory bodies could incentivize transplant institutions to provide social care by developing and reporting a “health equity” metric. ( 24 ) The NASEM committee underscored a final community‐focused social care activity, advocacy , which refers to work that changes policies that influence the availability of health and social services. In liver transplant, this advocacy work might target policies that determine the out‐of‐pocket expenses encountered by children/families after liver transplant.…”
Section: Opportunities For Social Care Intervention Researchmentioning
confidence: 99%